Oral health and nutrition - San Juan, Sofronio P.
This paper will discuss how dietary and nutritional standards are derived and utilized, as well as their effect on organogenesis. It will describe the relationship between dietary patterns and physical nature of foods, their roles in the etiology and prevention, and recommended counselling regimens of the two most common oral diseases... dental caries and periodontal disease. The significant nutritional considerations for the elderly, medically and immuno-compromised patients will be briefly explained.
Keywords: Diet nutrition; Oranogenesis; Dental caries; Dietary; Diet counseling; Periodontal disease